An architecture for large scale Internet measurement. - Paxson, V. (IEEE Communications magazine)
Historically, the Internet has been woefully under-measured and under-instrumented. The problem is only getting worse with the network's ever-increasing size. We discuss the goals and requirements for building a ?measurement infrastructure? for the Internet, in which a collection of measurement ?platforms? cooperatively measure the properties of Internet paths and clouds by exchanging test traffic among themselves. The key emphasis of the architecture, which forms the underpinnings of the National Internet Measurement Infrastructure (NIMI) project, is on tackling problems related to scale. Consequently, the architecture emphasizes decentralized control of measurements; strong authentication and security; mechanisms for both maintaining tight administrative control over who can perform what measurements using which platforms, and delegation of some forms of measurement as a site's measurement policy permits; and simple configuration and maintenance of platforms